Remediation of Heat Stress in Tomato (Lycopersicon Esculentum L.) by Foliar Application of Proline - Saeed Ur Rahman; Akbar Ali; Altaf Husssain; Sadia Nazeer; Mughees Ul Hassan; Waryam Abbas (Turkish Journal of Agriculture: Food Science and Technology)
The tomato is a significant vegetable in the world on the basis of consumption, nutrition, and extensive use in processed foods. During plant growth and development, amino acids especially exogenous application of proline (Pro), plays a crucial role to increase stress tolerance under various abiotic stresses. Among abiotic stressors, temperature is considered as an important and alarming stressor for plant development and growth. Sometime a significant drop in crop productivity is the outcome of harsh temperature increment. An investigation was carried out at the Horticulture Lab, College of Agriculture, University of Sargodha, during 2021-22 to inspect the role of foliar application of proline under heat stress in tomato plants. Tomato seedlings with true leaves were exposed to high temperatures (25°C [control], 40°C, and 45°C) with exogenous proline sprays of (0, 0.5, 1 and 1.5 mili-molars). Various growth attributes like morphological i-e number of leaves, leaf area cm2, shoot fresh weight (mg), shoot dry weight (mg), root fresh weight (mg), root dry weight (mg), and physiological [photosynthetic rate (µ mol/m-2s-1)], chlorophyll contents (spad), stomatal conductance (µ mols m-2 s-1 transpiration rate (µ mol/m-2 s-1),)] were studied. The findings indicated that foliar application of proline at 1.5 mM under heat stress on 40oC and 45oC was found to be more advantageous to improve growth attributes like number of leaves (12.2), leaf area (8.3 cm2), shoot length (10.39 cm), shoot fresh weight (1.88 mg), shoot dry weight (0.28 mg), root dry weight (0.20 mg), and remediated the detrimental effect of heat stress in tomato plants. The variation between control and proline treated heat-stressed plants supported that proline may have a function in alleviating heat stress.